Landscape Peluang dan Tantangan Keuangan Syariah di Indonesia - Muhammad Kahfi; Sahria Sahria; Jamaluddin Majid (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
Sharia finance is a financial system based on Islamic principles that prioritizes justice, transparency and the avoidance of prohibited elements such as usury, gharar and maysir. Sharia finance has enormous potential to be developed in Indonesia, which has the 2nd largest Muslim population in the world. This article discusses the opportunities and challenges of developing the sharia financial sector in Indonesia. This research uses a qualitative descriptive research method, with a library research approach which involves a series of activities related to collecting data from library sources. Efforts that need to be made to improve sharia financial institutions are to examine existing challenges and optimize existing opportunities.